Association between metabolic disorders and clinicopathologic features in endometrial cancer - Wang, Yuanpei; Liu, Qianwen; Sun, Yi; Wu, Weijia; Cheng, Xiaoran; Chen, Xuerou; Ren, Fang (Frontiers in Endocrinology, 2024)
Background: In recent years, the incidence of Endometrial cancer (EC) has been on the rise due to high-fat, high-calorie diets and low-exercise lifestyles. However, the relationships between metabolic disorders and the progression of EC remain uncertain. The purpose of our study was to explore the potential association between obesity, hypertension, hyperglycemia and clinicopathologic characteristics in EC patients.In categorical variables, Chi-square tests were used to calculate P values. Univariate logistic regression and multivariate logistic regression were used to identify the risk factors of myometrial invasion＞1/2 and lymph node metastasis. Overall survival (OS) was estimated using the Kaplan-Meier method.The study included 406 individuals with EC, 62.6% had type I and 37.4% had type II.Hypertension was seen in 132 (32.5%), hyperglycemia in 75 (18.5%), and overweight or obesity in clinicopathologic features of EC. Multivariate logistic regression revealed that hyperglycemia (OR=2.439,95% CI: 1.025-5.804, P = 0.044) was a risk factor for myometrial invasion depth >1/2 in patients with type I EC, and hypertension (OR=32.124,95% CI: 3.287-313.992, P = 0.003) was a risk factor for lymph node metastasis in patients with type I EC. Survival analysis found that hyperglycemia (P < 0.001) and hypertension (P = 0.002) were associated with OS in type I EC.Neither hyperglycemia, hypertension, nor obesity were associated with the prognosis in type II EC.Hyperglycemia was a risk factor for myometrial invasion depth >1/2 in patients with type I EC and hypertension was a risk factor for lymph node metastasis in patients with type I EC.Hypertension and hyperglycemia were associated with poor prognosis in patients with type I EC.